2017
DOI: 10.15406/ijrrt.2017.02.00038
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Styloid Process by Cone Beam Computed Tomography

Abstract: Objective: the aim of the study was to assess the length, angulations and the pattern of ossification of the Styloid process (SP) and to know if any correlation exists between them.Method: 50 patients of CBCT, TMJ views were considered, a total of 87tmjs were viewed using ORTHOPHOS XG3D X-ray system. The length, mediolateral (MLA), anteroposterior angulation (APA) was measured. The morphology was identified on 3D images. Person's Correlation coefficient was used for statistical analysis.Result: 0f the 87 scan.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
4
0
1
Order By: Relevance
“…In this study, the CBCT scans of 50 styloid processes distributed among 12 male and 13 female with a mean length of styloid processes 18.7 mm in male and 20.4 mm in female this results was close to a similar CBCT study on styloid processes assessment by Ilguy et al (13) with 22.2mm mean length. In many studies there was no significance difference between right and left side measurements, this study show close measurements between both side, 19.4mm mean of length at left side and 19.7 mm at right side which is in agreement with Ramadossand Sha (14) and Kosar et al (15) studies. In the present study the styloid process was classified morphologically according to number of ossified segments.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the CBCT scans of 50 styloid processes distributed among 12 male and 13 female with a mean length of styloid processes 18.7 mm in male and 20.4 mm in female this results was close to a similar CBCT study on styloid processes assessment by Ilguy et al (13) with 22.2mm mean length. In many studies there was no significance difference between right and left side measurements, this study show close measurements between both side, 19.4mm mean of length at left side and 19.7 mm at right side which is in agreement with Ramadossand Sha (14) and Kosar et al (15) studies. In the present study the styloid process was classified morphologically according to number of ossified segments.…”
Section: Discussionsupporting
confidence: 91%
“…(19) In our study, males showed higher mean values of the SHC length than females (32.9 mm and 31.8mm respectively) with no statistical significance. Similar values were reported by Ramadoss and Sha (25) where mean length was 32.10mm in males and 31.62mm in females. Many previous studies showed higher mean values of males than females with no significant difference.…”
Section: Discussionsupporting
confidence: 90%
“…(3,36) In the present study, no correlation was found between length and APA which agrees with previous reported results. (10,25) Further, no correlation was found between length and MLA similar to previous studies. (1,10,16,26) Also, no correlation was found between APA and MLA.…”
Section: Discussionsupporting
confidence: 73%
“…It is more precise than measurements through direct tracing. For this reasons the obtained results is more accurate and reliable than previous studies (8,14,(21)(22)(23)(24)(25)(26) . Each radiograph was measured twice and the measurement is recorded automatically when the program displays the individual values for each patient.…”
Section: Discussion:-supporting
confidence: 67%